Realizing more Crop per Drop through technological interventions - Rajput, T B S; Patel, Neelam (Indian Farming, 2018)
Sustainable development of land and water resources is very important for a country like India which shares 16% of the global population with only 2.4% of land and 4% of water resources. Efforts were therefore made to develop irrigation potential during the Plan periods. However, simultaneously efforts were not made to utilise irrigation water more efficiently. To meet the food security, income and nutritional needs of the projected population in 2050 the food production in the country will have to be almost doubled. Thus, judicious use of irrigation water is more important to enhance total production and area under irrigated agriculture. It can be achieved by introducing advance method of irrigation like micro-irrigation coupled with other improved water management practices.